Production and decomposition of leaf litter from forest species in silvopastoral systems, Valle del Sinu, Colombia - Tapia-Coronado, Jairo J.; Contreras, José L.; Martínez-Atencia, Judith; López, Leonardo; Rodríguez, José L. (Agronomía Mesoamericana, 2022)
Introduction. Traditional livestock production systems generate soil degradation, so it is important to implement silvopastoral systems as an alternative for meat and dairy cattle production. Objective. To quantify the production of leaf litter of perennial woody species (Gmelina arborea - Melina, Tabebuia rosea - Oak, Acacia mangium - Acacia) and the potential contribution of nutrients to the soil (nutrient cycling) within silvopastoral systems. Materials and methods. The production and decomposition of leaf litter of forest species was evaluated in fields planted with a variety of grasses of the genus Brachiaria, in the middle Sinu valley, Colombia, during May to September 2013. A randomized complete block design with three replications was used. The treatments used were Pr= Brachiaria hybrid cv. Mulato II, SSP1= Tabebuia rosea + Brachiaria cv. Mulato II, SSP2= Acacia mangium + Brachiaria cv. Mulato II, and SSP3= Gmelina arborea + Brachiaria cv. Mulato II. Results. The greater production of leaf litter in forest species within the silvopastoral systems was evidenced. The forest species G. arborea had the highest potential nutrient inputs in litterfall with the following descending pattern in kg ha-1: C 4069,6> Ca 96,47> N 62,46> K 37,48> Mg 23,60> P 14,57. Mulato II pasture litter and the forest species G. arborea exhibited higher decomposition rates (k= 1.87 and k=1.77, respectively) than the rest of the species evaluated. Conclusions. The forest species evaluated improved soil quality through a higher leaf litter input and a higher potential nutrient input.